Formation of new organometallic W/Cu/S clusters from reactions of [{(η5-C5Me5)WS3} 3Cu7(MeCN)9](PF6)4 with donor ligands. Crystal structures and optical limiting properties - Yu, H. (2014)
10.1016/j.jorganchem.2005.06.003